Quantum Dot Infrared Photodetectors: Photoresponse Enhancement Due to Potential Barriers - Mitin, Vladimir (Springer, 2010)
Potential barriers around quantum dots (QDs) play a key role in kinetics of photoelectrons. These barriers are always created, when electrons from dopants outside QDs fill the dots. Potential barriers suppress the capture processes of photoelectrons and increase the photoresponse. To directly investigate the effect of potential barriers on photoelectron kinetics, we fabricated several QD structures with different positions of dopants and various levels of doping. The potential barriers as a function of doping and dopant positions have been determined using nextnano(3) software. We experimentally investigated the photoresponse to IR radiation as a function of the radiation frequency and voltage bias. We also measured the dark current in these QD structures. Our investigations show that the photoresponse increases ~30 times as the height of potential barriers changes from 30 to 130 meV.